Development of Product Recycle Business Unit at Karang Taruna Sekar Arum Tunjungsekar - Arif Prasetyo Wibowo; Nurbani Yusuf; Eggy Fajar Andalas (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Efforts to improve the community's economy based on local potential are one of the focuses carried out by the government. The younger generation through youth organizations (Karang Taruna) are expected to be able to become the driving force for change in their area. In this service program, the service team conducted a service program for the development of recycle product business units at Karang Taruna Sekar Arum Tunjungsekar. This activity aims to change recycled waste so that it has use value in supporting the economy of the people in this region. The dedication method is carried out by discussion, practice, and mentoring methods. The result of the service is the creation of maggot business products which are widely marketed by the public by utilizing raw materials from household waste in this region. The resulting products are packaged in a modern way and marketed digitally. Therefore, it can be concluded that this community service activity was successful and able to increase the knowledge, skills, and income of the Tunjungsekar community through the utilization of Maggot waste and cultivation.